The Description of Stress Levels and Coping Strategies among Correctional Inmates in Class II A Detention Centers in Pekalongan City - Fadilla, Annisa Risky; kamalah, aisyah dzil (NHM PRESS, 2024)
Life in a correctional facility can lead to psychological issues among inmates, such as stress. According to the WHO, there are approximately 350 million people worldwide experiencing high levels of stress, making it the fourth most common health issue. Stress contributes to 40% of mental health problems among inmates. Therefore, effective coping strategies are crucial, as they help inmates manage stressors. This study aims to describe the stress levels and coping strategies of inmates at the Class II A Prison Pekalongan. This quantitative study employs a descriptive design, using total sampling with 124 respondents. Data were collected using the PSS-10 questionnaire to assess stress levels, the Brief COPE questionnaire to evaluate coping strategies, and a respondent characteristics questionnaire. Data analysis involved numerical and categorical analysis. The study found that the average age of respondents was 33.27 years. Most had been in the facility once, and the majority were male (93.5%). The most common marital status was married (46.0%), and the most frequent educational level was high school/vocational school (32.3%). The stress level among inmates was predominantly moderate, with 72.6% experiencing moderate stress. Most inmates used problem focused coping strategies (70.2%).